Design of an Augmented Reality Application to Improve Understanding of Spatial Structure in Elementary Schools - Syahrul Romadhon; Ika Asti Astuti; Buyut Khoirul Umri (Universitas Islam Indragiri, 2026)
Mathematics learning, particularly three-dimensional geometry in elementary schools, often requires students to visualize images presented in textbooks in order to understand the material, which can make it difficult for them to absorb the concepts being taught. This challenge is further compounded by the limited availability of interactive learning media and school policies that restrict the use of mobile devices as learning tools. These issues represent common obstacles in the implementation of effective geometry instruction at the elementary level. This study aims to design an Android-based Augmented Reality (AR) learning application to assist elementary school students in understanding abstract three-dimensional geometry concepts. The research methodology employed is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collection, development, testing, and distribution. The outcome of this study is an Android-based AR application for learning three-dimensional shapes. Black-box testing results indicate that all features—including marker scanning, display of 3D geometric objects, transformation into net forms, rotation, zoom in and zoom out, and instructional content for each type of three-dimensional shape—functioned properly. Furthermore, user evaluation was conducted using the System Usability Scale (SUS) method. The evaluation involved 10 respondents and produced an average score of 74, placing the application in the “Good” category. These results suggest that the application can serve as an effective interactive learning medium for elementary school education.